Critical empathy as teacher education reform : dissecting the principles that constrain socio-historical and moral vision - Lucey, Thomas A; Cooter, Kathleen Spencer, 1950- (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"This book considers teacher training in social studies and finds it lacking a sense of genuine critical empathy, a sense of shared humanity. Current teacher education generally defines critical thinking as processes examine topics in greater complexity, but does not prepare candidates to study, confront, and challenge existing social structures. Often in response to state mandates, teacher education programs rate and interpret candidate quality based on their conformance with standards and defined outcomes. There is a lack of tolerance for alternative views that might substantially challenge the often-oppressive hierarchical system of authority in our world. This volume written by social studies educators in the U.S., Canada and Australia offers the thinking and practice of teacher education scholars who embrace the idea and practices of empathy in the social studies classroom. Defined as "the ability to understand and share the feelings of another", direct emphasis on empathy represents a vehicle for developing a sense of mutual understanding and questioning of economic and social systems. Developing teacher candidates who comprehend and experience the feelings of diverse education stakeholders provides opportunities for harmonious teaching and learning environments situated in the lives of learners"--